Análisis del contenido cultural en la programación del RTV canal 3 de Vinces - Pazmiño Mayorga, Helen Briggitte (2020)
The present study analyzed the cultural content of Vinces's RTV channel 3 programming, as television is an influential entity in society. In order to obtain the information, this analysis focused on qualitative design, through descriptive and diagnostic research, through direct observation techniques where the programming of the said channel was studied and what the programs with cultural themes were determined. detecting in this way a shortage of said besides, it was found that they are mostly not of original production of this television station, since, having not contained local, the identity and cultural enrichment of the area is lost. With the results of this study it was concluded that further work should be carried out in common with education, through a pre-professional practice agreement with the Babahoyo Technical University, aimed at students of Social Communication, directed to students of Social Communication, since this way one will give the opportunity to the pupils so that they could develop workmanship and skills in the above mentioned career.